The Development of Competency-Based Curriculum of Education-Sandbox Pilot Schools: A Case Study of Government School Located on the Thai-Malaysian Border - Bin-alee, Nureeta; Maitreephun, Warapark (Journal of Education Studies, Chulalongkorn University, 2024)
Implementing a competency-based curriculum into practice is still novel at both the policy and practical levels for Thai Education. This study aimed to explore 1) The competency-based curriculum development process and 2) The factors promoting or hindering the success of implementing the competency-based curriculum policy in schools. This research employed the case study of a pilot school in an educational sandbox area located at the Thai-Malaysian border. An interview, observations, and document analysis were conducted for data collection. There were 11 key informants. The research instruments include a semi-structured interview, an observation form, and a document analysis form. Collected data was analyzed by using the content analysis technique. The period of this study was from September 2022 to April 2023. The research results showed that the school competency-based curriculum development process had three steps: 1) curriculum creation, which included 1.1) Training to understand the competency-based curriculum, 1.2) The creation of school concept, 1.3) Learning management unit design, and 1.4) Submitting for approval; 2) Curriculum implementation, which included 2.1) Curriculum administration, 2.2) Classroom instruction management, and 2.3) Support and promotion of the used curriculum; and 3) Curriculum Evaluation by using professional learning communities. The elements that promote success include the school director's competency and the community's readiness to accept the curriculum. The elements that hindered the success of implementation include the lack of clarity in learning evaluation and the lack of understanding of teachers’ learning management. Further study may consider the role of communities and stakeholders in developing competency-based curriculum.